Cue Reactivity to Electronic Cigarettes: A Systematic Review - Merel Keijsers; Maria Cecilia Vega-Corredor; Simon Hoermann; Melanie Tomintz (SAGE Publishing, 2022)
Cue reactivity to Electronic Nicotine Delivery Systems (ENDS) has been studied by several researchers, yet the variability in user types (smokers, former smokers, dual users, exclusive ENDS users) and ENDS designs used between the studies may have undermined consistent results. This systematic review aims to give an overview of ENDS cue reactivity and how smoking status and device design may moderate this. A systematic search of Medline, Embase, Web of Science, PubMed and Cochrane was completed. All studies which reported findings on reactivity to ENDS cues in the form of craving or desire for ENDS or cigarettes, attention to cue, delay of gratification or economic decisions were included. Exclusion criteria were non-human subjects, non-adult participants or participants with comorbidities. Literature selection was carried out by 2 independent reviewers. The risk of bias and study quality were assessed using tools developed by Cochrane, BMJ and NHLBI. A total of 711 papers were screened and 22 studies were included in the current review. Study design, research question(s), population of interest, number of participants, dependent variable(s), ENDS generation and nicotine content used and study results were extracted. ENDS cues reliably induced ENDS craving, with no clear moderation by smoking status and no apparent moderation by device generation. In about half of the studies, ENDS cues induced craving for conventional cigarettes. Most studies used a smoker sample, thus limiting the conclusions that can be drawn on the moderation of cue reactivity by smoking status. The quality varied among studies but comparing the findings against the outcomes of only high-quality studies did not yield any different results. The results of this review support the notion of cue reactivity to ENDS, identifies gaps in current research on different user types and implies that ENDS design iterations have little impact on cue reactivity.